A rapid method to estimate microbial activity in biofilter biofilm using hydrogen peroxide degradation - Lars-Flemming Pedersen (Aquaculture International, 2025)

Effects of drum filters, swirl separators and foam fractionation on water quality in pilot scale recirculating aquaculture systems - Kim João de Jesus Gregersen; Lars-Flemming Pedersen (Aquacultural Engineering, 2025)

Effective nitrification and removal of particulate organic matter in biofilters with compressible polyurethane foam - Bence Dániel Kovács; Kim João de Jesus Gregersen; Lars-Flemming Pedersen (Aquacultural Engineering, 2025)

Testing of a passive foam fractionator prototype in a commercial recirculating trout farm - Kim João de Jesus Gregersen; Lars-Flemming Pedersen (Aquacultural Engineering, 2025)

Estimating biofilm activity on biofilter elements in recirculating aquaculture systems (RAS) for rearing Atlantic salmon parr (Salmo salar) during operation with ozone and peracetic acid - Wanhe Qi; Peter Vilhelm Skov; Kim João de Jesus Gregersen; Samaneh Mousavi; Lars-Flemming Pedersen; Vasco C. Mota (Aquaculture, 2025)

Comparison of four different types of biomedia during start-up in a recirculating aquaculture system with rainbow trout - Mang'era Samwel Mnyoro; Renalda N. Munubi; Sebastian W. Chenyambuga; Lars-Flemming Pedersen (Journal of Water Process Engineering, 2024)

Towards sustainable water disinfection with peracetic acid in aquaculture: A review - Dibo Liu; David L. Straus; Lars‐Flemming Pedersen; Christopher Good; Carlo C. Lazado; Thomas Meinelt (Reviews in Aquaculture, 2024)
Peracetic acid (PAA) has a long history as an efficacious and eco‐friendly disinfectant. It was first synthesised in 1902, and since then a wide range of applications has been developed in various industries. Aquaculture is a more recent industry wherein the potential of PAA is significant. As the global demand for sustainable development increases, there has likewise been growing interest in using PAA in aquaculture as an alternative to less environmentally friendly practices. PAA has no carcinogenic risk to humans (unlike formalin), has negligible harmful by‐products (unlike chlorine‐based disinfectants) and with appropriate precautions, the risks of causing severe human health damage is easier to control than ozone. Fish show strong physiological recovery and adaptation to PAA, whereas susceptible life stages of pathogens are highly vulnerable, enabling a safe and efficacious disinfection of the entire culture water and not the flow‐restricted disinfection by such processes as ultraviolet radiation or ozone. The effective concentration of PAA against many fish pathogens is usually below 2 mg L −1 , which is tolerable for most fish, and it has very low environmental risk due to rapid degradation. However, such degradation and the hydrodynamics in production‐scale aquaculture systems complicate the practical use of PAA. In this review, we summarise key results of safe concentrations of PAA and its effectiveness specifically for fish farmers. We also outline major difficulties and possible solutions for practical uses of PAA. We intend to bring global attention to this compound and inspire future possibilities for its sustainable use as a water disinfectant in aquaculture.

Peracetic acid mode-of-action on aquaculture microbes evaluated by dual-staining flow cytometry - Sanni L. Aalto; Lone Madsen; Lars-Flemming Pedersen (Aquaculture, 2024)

A case study comparing the addition of two different carbon sources in pilot scale RAS with trout with and without biofilters - Kim João de Jesus Gregersen; Lars-Flemming Pedersen (Aquacultural Engineering, 2023)

Evaluating protein skimmer performance in a commercial seawater recirculating aquaculture system (RAS) - Bence Dániel Kovács; Kim João de Jesus Gregersen; Florian Rüppel; Arndt von Danwitz; Lars-Flemming Pedersen (Aquacultural Engineering, 2023)

Post-release effects of catch and release angling for sea trout: Mortality, growth and wound healing - Christian Skov; Keno Ferter; Niels Jepsen; Lars-Flemming Pedersen; Wolf-Christian Lewin; Casper Gundelund; Marc Simon Weltersbach (Fisheries Research, 2023)

Effect of water hardness on peracetic acid toxicity to zebrafish, Danio rerio, embryos - Pierre-André Marchand; David L. Straus; Andreas Wienke; Lars-Flemming Pedersen; Thomas Meinelt (Aquaculture International, 2013)